Unveiling women's motivations: the allure of alt-right media - McGhee, Mara (Kansas State University, 2024)
Alt-right ideology has become increasingly mainstream despite its dangerous and regressive core (Valasik and Reid, 2023). The messages circulated by alt-right public figures (politicians, influencers, etc.) are often self-described as anti-woke and spread harmful ideology with the focus of oppressing marginalized groups or incite violence either directly or indirectly. One of the groups targeted by the alt-right are women. However, there are women who still consume alt-right media despite the harm it causes. This study will apply Uses and Gratifications Theory to examine why everyday people, especially women, consume alt-right media and the role parasocial relationships play in alt-right media consumption.
Keywords: Alt-right; Parasocial relationships; Uses and Gratifications Theory; Media